2007
DOI: 10.2478/v10001-007-0026-0
|View full text |Cite
|
Sign up to set email alerts
|

The Concentration of Selected Cancer Markers (TPA, TPS, Cyfra 21-1, CEA) in Workers Occupationally Exposed to Arsenic (As) and Some Heavy Metals (Pb, Cd) During a Two-Year Observation Study

Abstract: The strong positive correlation between blood concentrations of Cd and CEA, the marker of abnormal cellular differentiation, may reflect neoplastic transformation of normal cells stimulated by some carcinogens (e.g. cadmium). All the examined carcinogenic, or potentially carcinogenic metals (As, Cd, Pb) belong to the group of factors having impact on serum TPS and/or TPA concentrations in exposed workers. No correlation was found between CYFRA 21-1 and any metal studied but it is plausible that changes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Although cadmium and lead are found in extremely low levels in preindustrial humans, and no function for these elements is known in the human body (Needleman, 2004), they are known to accumulate in teeth, particularly in outer enamel (Cleymaet et al, 1191; Costa de Almeida el al., 2007) and inner dentin (Grandjean and Jorgensen, 1990), apparently according to the level of exposure. In humans, Cd exposures have been associated with a number of diseases, such as end‐stage renal failure, early onset of diabetic renal complications, osteoporosis, deranged blood pressure regulation, and increase cancer risk (Jarup et al, 1998; Nakagawa and Nishijo, 1996; Sharara et al, 1998; Szymańka‐Chabowska et al, 2007). This element has been classified as a carcinogen by the International Agency for Research on Cancer (IARC) (Magos, 1991) and functions as a teratogenic agent, and it can harm the reproductive system (Vahter et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cadmium and lead are found in extremely low levels in preindustrial humans, and no function for these elements is known in the human body (Needleman, 2004), they are known to accumulate in teeth, particularly in outer enamel (Cleymaet et al, 1191; Costa de Almeida el al., 2007) and inner dentin (Grandjean and Jorgensen, 1990), apparently according to the level of exposure. In humans, Cd exposures have been associated with a number of diseases, such as end‐stage renal failure, early onset of diabetic renal complications, osteoporosis, deranged blood pressure regulation, and increase cancer risk (Jarup et al, 1998; Nakagawa and Nishijo, 1996; Sharara et al, 1998; Szymańka‐Chabowska et al, 2007). This element has been classified as a carcinogen by the International Agency for Research on Cancer (IARC) (Magos, 1991) and functions as a teratogenic agent, and it can harm the reproductive system (Vahter et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Arsenic is a small constituent of cigarette smoke; however, this element was the first metal (semimetal) identified as a carcinogen (Magos, 1991). Epidemiological studies have shown association between arsenic exposure and cancer of the skin and various internal organs (Magos, 1991; Szymańka‐Chabowska et al, 2007). That element can cause hyperkeratosis, pigmentation changes, effects on the liver and circulatory and nervous systems, and chronic cough (Vahter et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In our pilot study we already found a positive association between serum CEA and an index of internal exposure based on blood levels of lead, marker PCBs and dioxin like activity, and on urinary levels of cadmium and 1-OHP [ 4 ]. Positive correlations between serum CEA levels and urinary 1-OH-P [ 33 ] and between blood levels of cadmium and CEA [ 66 ] were described previously. A positive association between CEA and smoking or alcohol consumption was reported by Verdi et al .…”
Section: Discussionmentioning
confidence: 94%
“…In 2002, the International Agency for Research on Cancer (IARC) has classified As in drinking water as a group 1 human carcinogen [148]. Besides the induction of different types of cancer (skin, bladder, liver, kidney, and lung) [149, 150], sublethal exposure to As can cause severe human health problems such as diabetes [151] and neurological diseases (Alzheimer and Parkinson's) [152, 153]. While epidemiological studies have clearly demonstrated the harmful effects of As with respect to the induction of human diseases, the mechanisms of toxicity remain largely unknown except ROS generation [154].…”
Section: Ape1 As a Prediction Marker Of Environmental Carcinogenesmentioning
confidence: 99%